Hidden Armour: The Passive Protective Function of Caudal Osteoderms in Snakes - Frýdlová, Petra; Dudák, Jan; Tymlová, Veronika; Žemlička, Jan; Moravec, Jiří; Frynta, Daniel (Journal of morphology, 2025)
Dermal armour, consisting of bony dermal structures known as osteoderms (ODs), is widespread in squamate reptiles. However, in some limbless taxa such as snakes, ODs are rare, probably due to a trade-off between mechanical protection and the demands of locomotion and consumption of large prey. Recent findings of ODs restricted to the distal body regions of sand boas (Eryx, Erycidae) challenge this paradigm, suggesting they provide passive mechanical protection against aggressive prey without significantly impairing locomotion. Building on these findings, we have continued the search and identified three additional snake species that have well-developed caudal ODs, including the first-ever discovery of ODs in shield-tailed snakes (Uropeltidae). In these fossorial species, which are characterised by their unique tail morphology, ecological adaptations and colouration, the ODs at the tail tip may serve as passive protection against predators. However, an alternative role in locomotion or occasional phragmosis cannot be ruled out. In the Javelin sand boa (Eryx jaculus), the ODs are hypothesised to function as a mechanical defence against aggressive prey. These results highlight the functional and evolutionary plasticity of ODs and emphasise the urgent need for further studies on their specific role and adaptive significance in the ecology and evolution of snakes.
Keywords: Predatory Behavior; lokomoce; Phylogeny; predátorské chování; Biological Evolution; Bone and Bones; Tail; kosti a kostní tkáň; dermal armour; zvířata; µCT; osteoderms; fylogeneze; biologická evoluce; antipredatory strategy; hadi; Locomotion; Animals; Squamata; Snakes; ocas